Current therapeutic concepts in peripartum cardiomyopathy - Krejci, Jan; Poloczkova, Hana; Nemec, Petr (Current pharmaceutical design, 2015)
Peripartum cardiomyopathy (PPCM) is a relatively rare disease characterized by systolic heart failure occuring towards the end of pregnancy or during the months following birth. It is most often seen in women of African descent, and its incidence seems to be slightly increasing in recent years. Other etiologies of heart failure should be excluded to determine the diagnosis of PPCM. The clinical picture corresponds to systolic heart failure. The rapid onset of the symptoms in relation to pregnancy is striking. The essential diagnostic procedures such as echocardiography, cardiac magnetic resonance imaging and endomyocardial biopsy may be beneficial in certain situations. The etiology of the disease remains unclear. Speculated causes include myocarditis, autoimmune disorders, cardiotropic virus infection, and abnormal responses to hemodynamic and hormonal changes during pregnancy. Particular attention is currently given to the concept of increased oxidative stress inducing production of proapoptotic, angiostatic and proinflammatory mediators. Recovery of left ventricular systolic function occurs in about half of the cases. Mortality has been decreasing in recent years, especially in the United States, but is still between 10-15% in less developed countries where therapeutic possibilities are limited. In addition to standard heart failure therapy, specific treatments (pentoxyfilline, bromocriptine, immunomodulatory therapy) have been tested. Mechanical circulatory support is sometimes needed. Heart transplantation is the therapeutic option for the most severe heart failure and is used in about 10% of the cases. Recurrence in subsequent pregnancy is common and therefore, another pregnancy is not recommended in many cases.
Keywords: kardiomyopatie; peripartální období; Humans; Cardiomyopathies; lidé; Peripartum Period